Budaya Kerja Berwawasan Cinta Lingkungan pada Pengikut Tarekat Qadiriyyah Wa Naqsyabandiyyah Kepulauan Meranti - Masduki Masduki; Toni Hartono (An-Nida', 2013)
means take some effort to address the human spiritual disease. Therefore, it is important to restore (restoration) also farther more important is the emphasis on philosophical solution that focuses